Occult parametrial metastasis in operable cancer cervix: is a routine radical hysterectomy justified? - Jose, Tony; Chawla, Sushil; Seth, Atul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Operable Ca cervix is treated by a Type III Radical hysterectomy(RH) with pelvic lymphadenectomy and comprises of a complex parametrial resection (PR) due to the possibility of occult parametrial metastasis(OPM) leading to high post-operative and delayed morbidity especially after adjuvant radiotherapy(RT). If risk factors for OPM were known, a less radical procedure could be performed in low risk patients thus minimizing the morbidity. Methods: A retrospective study was carried out to evaluate the incidence of OPM in operated patients and to study the risk factors associated with OPM and explore the theoretical feasibility of doing a type I hysterectomy in low risk patients. Results: The incidence of OPM was 16.1% in all stages (0% in IA, 10.71% in IB1, 33.3% in Stage IB2 and 18.8 % in IIA1). Primary tumor diameter (PTD) and LNM were the most statistically significant risk factors for OPM. 90% of patients with OPM also had lymph node metastasis (LNM). In this study, all patients with OPM had other risk factors for adjuvant treatment. Conclusions: Small size early stage tumors may be considered for less radical surgery in the absence of obvious intermediate risk factors. A node dissection with negative frozen section during surgery can finally select patients for a simple hysterectomy(SH). More evidence from randomized trials are needed to evaluate the oncological safety of a less radical procedure and define the type of surgery to be done.